Bright Coppertunities: Multinuclear CuI Complexes with N–P Ligands and Their Applications. Issue 22 (22nd April 2014) - Wallesch, Manuela; Volz, Daniel; Zink, Daniel M.; Schepers, Ute; Nieger, Martin; Baumann, Thomas; Bräse, Stefan
Abstract Easy come, easy go: the great structural diversity of CuI complexes is an ambivalent trait. Apart from the well‐known catalytic properties of CuI, a great number of potent luminescent complexes have been found in the last ten years featuring a plethora of structural motifs. The downside of this variety is the undesired formation of other species upon processing. In here, strategies to avoid this behavior are presented: Only one favorable structural unit often exists for multinuclear CuI complexes with bridging ligands. In addition, these complexes exhibit favorable photophysical properties due to cooperative effects of the metal halide core. Furthermore, we demonstrate the broad range of applications of emitting CuI compounds.